Phosphoinositide 3-kinase: a critical signalling event in pulmonary cells - Condliffe, Alison M (BioMed Central, 2000)
Phosphoinositide 3-kinases (PI-3Ks) are enzymes that generate lipid second messenger molecules, resulting in the activation of multiple intracellular signalling cascades. These events regulate a broad array of cellular responses including survival, activation, differentiation and proliferation and are now recognised to have a key role in a number of physiological and pathophysiological processes in the lung. PI-3Ks contribute to the pathogenesis of asthma by influencing the proliferation of airways smooth muscle and the recruitment of eosinophils, and affect the balance between the harmful and protective responses in pulmonary inflammation and infection by the modulation of granulocyte recruitment, activation and apoptosis. In addition they also seem to exert a critical influence on the malignant phenotype of small cell lung cancer. PI-3K isoforms and their downstream targets thus provide novel therapeutic targets for intervention in a broad spectrum of respiratory diseases.